Association between the triglyceride glucose index and heart failure: NHANES 2007–2018 - Zhang, Fudan; Hou, Xu (Frontiers in Endocrinology, 2024)
Background: Patients with heart failure (HF) were compared with non-heart failure people to explore the relationship between triglyceride glucose index (TyG) and HF in participants with cardiovascular and cerebrovascular diseases. Methods: TyG index was calculated as ln [fasting triglyceride (mg/dL) × fasting glucose (mg/dL)/2].Multivariate Logistic regression models were used to investigate the association between TyG index and the risk of HF. Restricted cubic spline (RCS) analysis was applied to evaluate the dose-response relationship between TyG index and the risk of HF.Results: National Health and Nutrition Examination Survey (NHANES) (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) were used to analyze the association between TyG and HF in patients. A total of 13825 participants who had TyG index measured were included, involving 435 individuals with HF and 13390 non-HF population. HF people had higher levels of TyG index compared with those in the non-HF people (8.91±0.74 vs 8.57±0.66，p<0.001). The odds ratio (OR) of HF for TyG index from logistic regression was 1.644, and 1.057 in model 1(without adjusting for any variables), and 4(adjusted for all covariates), respectively. Compared with individuals with Q1, higher TyG index was related to the increased risk of HF. The Model 1 showed that there was a linear dose-response relationship between TyG index and HF(p=0.686). The TyG index predicted the area of the Receiver operating characteristic (ROC) curve of 0.602(95%CI:0.575-0.629, p<0.001) and the optimal cut-off value was 8.91.TyG index was positively associated with the risk of HF. TyG index may be a therapeutic target and an important predictor of HF.